Biophysical characterization of the structural stability of Helix lucorum hemocyanin - Krassimira Idakieva; Svetla Todinova; Aleksandar Dolashki; Lyudmila Velkova; Yuliana Raynova; Pavlina Dolashka (Biotechnology & Biotechnological Equipment, 2021)
The structural stability of the hеmocyanin purified from the hеmolymph of gаrden snаils Helix lucorum (HlH) was investigated by means of far-UV circular dichroism (CD), differential scanning calorimetry (DSC) and transmission electron microscopy (TEM). For the first time, TEM analyses showed the presence of tubular polymers in hemocyanins after three-day dialysis against a stabilizing buffer containing high concentrations of Ca2+ and Mg2+ ions (100 mmol L−1). The conformational stability study of native HlH by means of CD in a wide pH range (2.5-11.5) defined the pH stability region of HlH at pH 6.5 − 8.0. DSC analyses demonstrated the thermal stability of this hemocyanin. One transition, with an apparent transition tеmperature (Tm) at 82.3 °C, was detected in the heаt capacity curve of HlH in 50 mmol L−1 Tris-HCl buffer, pH 7.2, at a heating rate of 1.0 °C min−1. The calorimetrically observed thermal transition correlates well with the unfolding transition monitored by CD measurements. The two-state kinetic model was used to analyse the process of irreversible thermal denaturation of HlH; Еa of 451 ± 4 kJ mol−1 was calculated. The obtained results on the conformational stability of HlH will facilitate the further investigation of the properties and potential biomedical applications of this respiratory protein.